Hot stamp member
The Al-Si alloy and surface plating layer composition in the hot stamping steel plate addresses hydrogen embrittlement issues in Al-plated steel sheets, ensuring effective hydrogen suppression and improved productivity in high dew point environments.
Patent Information
- Application Number
- JP2024164135
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-04-06
- Filing Date
- 2024-09-20
- Publication Date
- 2025-01-23
- Estimated Expiration
- 2042-03-30
AI Technical Summary
Existing hot stamping technologies face challenges with hydrogen penetration into Al-plated steel sheets, especially in high dew point environments, leading to hydrogen embrittlement and reduced productivity due to scale removal processes.
A hot stamping steel plate with an Al-Si alloy plating layer and a surface plating layer composed of Sn, Ni, and Zn, with specific chemical compositions and thicknesses, designed to suppress hydrogen intrusion and enhance adhesion, even in uncontrolled dew point conditions.
Effectively prevents hydrogen penetration into the steel sheet during and after hot stamping, improving productivity by eliminating the need for scale removal and enhancing the strength and durability of the hot stamping member.
Smart Images

Figure 2025011114000021 
Figure 2025011114000022 
Figure 2025011114000023
Abstract
Description
[Technical field]
[0001] The present invention relates to a steel sheet for hot stamping and a hot stamping member. This application claims priority based on Japanese Patent Application No. 2021-064884 filed on April 6, 2021, the contents of which are incorporated herein by reference. [Background technology]
[0002] In recent years, there has been a demand for reducing the weight of automobile bodies from the viewpoint of environmental protection and resource saving, and the application of high-strength steel sheets to automobile components has accelerated. Automotive components are manufactured by press forming, but as the strength of steel sheets increases, not only does the forming load increase but also the formability decreases, making the formability of high-strength steel sheets into components with complex shapes an issue. To solve this issue, the application of hot stamping technology, in which steel sheets are heated to a high temperature in the austenite region where they soften and then press formed, is being promoted. Hot stamping is attracting attention as a technology that achieves both formability into automobile components and ensuring the strength of automobile components by performing quenching treatment in a die simultaneously with press working.
[0003] When hot stamping is performed on a bare steel sheet that has not been plated or the like, it is necessary to perform the hot stamping in a non-oxidizing atmosphere in order to suppress the formation of scale and surface decarburization during heating. However, even if hot stamping is performed in a non-oxidizing atmosphere, since the atmosphere is air from the heating furnace to the press, scale is formed on the surface of the steel sheet after hot stamping. This scale on the surface of the steel sheet has poor adhesion and easily peels off, so there is a concern that it may have a negative effect on other processes. Therefore, it is necessary to remove it using shot blasting or the like. Shot blasting has a problem of affecting the shape of the steel sheet. In addition, there is a problem that the productivity of the hot stamping process is reduced by the scale removal process.
[0004] One method for improving the adhesion of scale on the surface of a steel sheet is to form a plating layer on the surface of the steel sheet. By forming a plating layer, a scale with good adhesion is formed on the surface of the steel sheet even when hot stamping is performed, so a scale removal process is not required. Therefore, by forming a plating layer, the productivity of the hot stamping process is improved.
[0005] As a method for plating the surface of steel sheets, Zn plating or Al plating can be used, but when Zn plating is used, there is a problem of liquid metal embrittlement (hereinafter referred to as LME). LME is a phenomenon in which a solid metal that is inherently ductile becomes embrittled when tensile stress is applied to the solid metal surface in contact with liquid metal. Zn has a low melting point, and during hot stamping, molten Zn penetrates along the prior austenite grain boundaries of Fe, causing microcracks in the steel sheet.
[0006] When aluminum plating is applied to steel sheets, the above-mentioned LME problem does not occur, but aluminum reacts with water on the aluminum plating surface during hot stamping, generating hydrogen. This causes a problem of a large amount of hydrogen penetrating into the steel sheet. If a large amount of hydrogen penetrates into the steel sheet, the steel sheet will crack when stress is applied after hot stamping (hydrogen embrittlement).
[0007] Patent Document 1 discloses a technique for suppressing hydrogen penetration into steel at high temperatures by enriching the surface region of the steel sheet with nickel.
[0008] Patent Document 2 discloses a technique for suppressing hydrogen penetration into a steel material by coating the steel sheet with a barrier precoat containing nickel and chromium and having a weight ratio Ni / Cr of 1.5-9.
[0009] However, the method of Patent Document 1 was not always able to sufficiently suppress the penetration of hydrogen that occurs when Al plating is applied. Moreover, the method of Patent Document 2 was not always able to sufficiently suppress the penetration of hydrogen into the steel sheet in an environment where dew point control is not performed (for example, in a high dew point environment such as 30°C). Furthermore, if an Al-plated steel sheet is used in an environment where the steel sheet corrodes after hot stamping, a large amount of hydrogen may accumulate in the steel sheet, which is thought to be the cause of delayed fracture. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] Japan Special Publication No. 2017-525849 [Patent Document 2] Japan Special Publication No. 2019-518136 Summary of the Invention [Problem to be solved by the invention]
[0011] The present invention has been made in view of the above problems, and has an object to provide a hot-stamped member that can suppress hydrogen penetration even in a high dew-point environment when hot stamping an aluminum-plated steel sheet and is excellent in suppressing hydrogen penetration into the steel sheet after hot stamping, as well as a steel sheet for hot stamping from which the hot-stamped member can be manufactured. [Means for solving the problem]
[0012] As a result of intensive research, the present inventors have found that, when a steel sheet for hot stamping having an Al-Si alloy plating layer is provided with a surface plating layer having a desired chemical composition and thickness, the amount of hydrogen penetrating into the steel sheet for hot stamping can be sufficiently suppressed even when hot stamping is performed in an environment where the dew point is not controlled, and the amount of hydrogen penetrating into the steel sheet after hot stamping can be easily suppressed.
[0013] The present invention was made based on the above findings and through further investigation, and the gist of the present invention is as follows. (1) A steel sheet for hot stamping according to one embodiment of the present invention comprises a base steel sheet, an Al-Si alloy plating layer having an Al content of 75 mass% or more, an Si content of 3 mass% or more, and a sum of the Al content and the Si content of 95 mass% or more, An aluminum oxide coating having a thickness of 0 to 20 nm; a surface plating layer having a total of Sn content, Ni content and Zn content exceeding 90% by mass, an Sn content of 10% by mass or more, an Ni content of less than 90% by mass, and a Zn content of less than 50% by mass; In this order, The thickness of the Al-Si alloy plating layer is 5 to 50 μm, The thickness of the surface plating layer is more than 300 nm and is 2500 nm or less. 2. A steel sheet for hot stamping comprising:
[0014] (2) In the steel sheet for hot stamping described in the above (1), the surface plating layer may be provided as an upper layer on the Al-Si alloy plating layer in direct contact with the Al-Si alloy plating layer.
[0015] (3) In the steel sheet for hot stamping described in the above (1), the aluminum oxide coating may have a thickness of 2 to 20 nm.
[0016] (4) The steel sheet for hot stamping according to any one of (1) to (3) above, The chemical composition of the base steel sheet is, in mass%, C: 0.25 to 0.70%, Si: 0.005 to 1.000%, Mn: 0.30-3.00%, P: 0.100% or less, S: 0.1000% or less, N: 0.0100% or less, Cu: 0-1.00%, Ni: 0-1.00%, Cr: 0~1.000%, Mo: 0~1.000%, Nb: 0 to 0.200%, V: 0 to 1.000%, Ti: 0 to 0.150%, B: 0~0.0100%, Co: 0-1.00%, W: 0 to 1.00%, Sn: 0-1.00%, Sb: 0 to 1.00%, Zr: 0-1.00%, Mg: 0 to 0.150%, Al: 0 to 1.0000%, Ca: 0 to 0.010%, REM: 0% to 0.300%, and The balance may be Fe and impurities.
[0017] (5) The steel sheet for hot stamping described in (4) above is The chemical composition of the base steel plate is, in mass%, Cu: 0.01 to 1.00%, Ni: 0.01 to 1.00%, Cr:0.001~1.000% below, Mo: 0.001 to 1.000%, Nb: 0.001 to 0.200%, V: 0.01 to 1.00%, Ti: 0.001 to 0.150%, B: 0.001 to 0.0100%, Co: 0.01 to 1.00%, W: 0.01 to 1.00%, Sn: 0.01 to 1.00%, Sb: 0.01 to 1.00%, Zr: 0.01 to 1.00%, Mg: 0.001 to 0.150%, Al: 0.0010 to 1.0000%, Ca: 0.001 to 0.010%, and REM: 0.001 to 0.300% The resin may contain one or more selected from the group consisting of:
[0018] (6) A hot stamped member according to one aspect of the present invention comprises: A hot stamped member comprising a base steel material and a plating layer provided on the base steel material, the plating layer comprising: a surface-rich region in which the sum of the Sn content, the Ni content, and the Zn content is 50% by mass or more, the Sn content is 7% by mass or more, the Ni content is less than 72% by mass, and the Zn content is less than 40% by mass; an Al-rich region in which the sum of the Sn content, the Ni content, and the Zn content is less than 50 mass%, the Al content is 10 mass% or more, and the Fe content is 50 mass% or less; an Fe-rich region having an Al content of 10 mass% or more and an Fe content of more than 50 mass%; in this order from the surface of the plating layer, In a region from the surface of the plating layer to a position 100 nm from the surface of the plating layer in a thickness direction, The maximum total value of the Sn content, Ni content and Zn content is 50 mass% or more, The Fe content is 10 mass% or less, In a region of the plating layer from a position 100 nm from the surface in the thickness direction to a position 500 nm from the surface in the thickness direction, The maximum total value of the Sn content, Ni content and Zn content is 5 mass% or more, The Fe content is 40 mass% or less, In a region of the plating layer from a position 500 nm from the surface in the thickness direction to a position 1000 nm from the surface in the thickness direction, The maximum total value of the Sn content, Ni content and Zn content is 1 mass% or more, The Fe content is 50 mass% or less.
[0019] (7) In the hot stamped member according to (6) above, the Ni content in the surface rich region may be less than 50 mass %.
[0020] (8) The hot-stamped member according to (6) or (7) above, In a region from the surface of the plating layer to a position 20 nm from the surface of the plating layer in the thickness direction, At least one of Sn oxide, Sn hydroxide, Ni oxide, Ni hydroxide, Zn oxide, and Zn hydroxide may be present, and the total of the Sn content, Ni content, and Zn content may be 30 mass% or more.
[0021] (9) The hot stamped member according to any one of (6) to (8) above, The chemical composition of the base steel is, in mass%, C: 0.25-0.70%, Si: 0.005 to 1.000%, Mn: 0.30-3.00%, P: 0.100% or less, S: 0.1000% or less, N: 0.0100% or less, Cu: 0-1.00%, Ni: 0-1.00%, Cr: 0~1.000%, Mo: 0~1.000%, Nb: 0 to 0.200%, V: 0 to 1.00%, Ti: 0 to 0.150%, B: 0~0.0100%, Co: 0-1.00%, W: 0 to 1.00%, Sn: 0-1.00%, Sb: 0 to 1.00%, Zr: 0-1.00%, Mg: 0 to 0.150%, Al: 0 to 1.0000%, Ca: 0 to 0.010%, REM: 0% to 0.300%, and The balance may be Fe and impurities.
[0022] (10) The hot stamped member according to (9) above, The chemical composition of the base steel is, in mass%, Cu: 0.01 to 1.00%, Ni: 0.01 to 1.00%, Cr:0.001~1.000% below, Mo: 0.001 to 1.000%, Nb: 0.001 to 0.200%, V: 0.01 to 1.00%, Ti: 0.001 to 0.150%, B: 0.0010~0.0100%, Co: 0.01 to 1.00%, W: 0.01 to 1.00%, Sn: 0.01 to 1.00%, Sb: 0.01 to 1.00%, Zr: 0.01 to 1.00%, Mg: 0.001 to 0.150%, Al: 0.0010 to 1.0000%, Ca: 0.001 to 0.010%, and REM: 0.001 to 0.300% The resin may contain one or more selected from the group consisting of: Effect of the Invention
[0023] According to the above-described aspects of the present invention, even when an Al-plated steel sheet is hot stamped, hydrogen penetration can be suppressed even in a high dew point environment, and a hot stamped member that is excellent in suppressing hydrogen penetration into the steel sheet after hot stamping can be provided, as well as a steel sheet for hot stamping from which the hot stamped member can be manufactured. [Brief description of the drawings]
[0024] [Figure 1] FIG. 1 is a cross-sectional schematic view of a steel sheet for hot stamping according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view of a steel sheet for hot stamping according to another embodiment of the present invention. [Diagram 3] 1 is an example of a measurement result of glow discharge optical emission spectrometry of a hot stamped member. [Figure 4] 1 is an example of a measurement result of glow discharge optical emission spectrometry of a hot stamped member. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0025] <Steel sheets for hot stamping> As a result of extensive investigations, the inventors have found that in an environment where the dew point is not controlled, when a steel sheet having an aluminized coating is hot stamped, the aluminum on the aluminized surface reacts with water in the air, generating a large amount of hydrogen and causing a large amount of hydrogen to penetrate into the steel sheet.
[0026] As a result of further intensive investigations, the present inventors have obtained the following findings. (A) When a plating having a total content of Sn, Ni and Zn exceeding 90 mass%, an Sn content of 10 mass% or more, an Ni content of less than 90 mass%, and a Zn content of less than 50 mass% is used as a surface plating layer, it is possible to suppress the penetration of hydrogen into the steel sheet during hot stamping at a high dew point. (B) When the thickness of the surface plating layer is more than 300 nm and not more than 2500 nm, the reaction with water in the atmosphere is sufficiently suppressed, and the amount of hydrogen that penetrates into the steel sheet can be reduced.
[0027] In the hot stamping steel sheet according to the present embodiment, the configuration of the hot stamping steel sheet was determined based on the above findings. The hot stamping steel sheet according to the present embodiment achieves the intended effect of the present invention by the synergistic effect of each plating configuration. The hot stamping steel sheet 10 includes a base steel sheet 1, an Al-Si alloy plating layer 2, and a surface plating layer 4 in this order, as shown in FIG. 1. When an Al oxide coating is provided, the hot stamping steel sheet 10A includes a base steel sheet 1, an Al-Si alloy plating layer 2, an Al oxide coating 3, and a surface plating layer 4 in this order, as shown in FIG. 2. Each configuration will be described below. In this specification, a numerical range expressed by using "to" means a range including the numerical values described before and after "to" as the lower and upper limits. The numerical values indicated by "less than" and "more than" do not include the numerical range. All % for chemical composition indicates mass %.
[0028] (base steel plate) The steel sheet (base steel sheet) 1 of the hot stamping steel sheet 10 according to this embodiment may have the chemical composition of a known hot stamping steel sheet, for example, the chemical composition is, in mass %, C: 0.25% to 0.70%, Si: 0.005% to 1.000%, Mn: 0.30% to 3.00%, P: 0.100% or less, S: 0.1000% or less, N: 0.0100% or less, Cu: 0% to 1.00%, Ni: 0% to 1.00%, Cr: 0% to 1.000%, Mo: 0% to 1.000%, Nb: 0% to 0.200%, V: 0%. ~1.00%, Ti: 0%-0.150%, B: 0%-0.0100%, Co: 0%-1.00%, W: 0%-1.00%, Sn: 0%-1.00%, Sb: 0%-1.00%, Zr: 0%-1.00%, Mg: 0%-0.150%, Al: 0%-1.0000%, Ca: 0%-0.010% and REM: 0%-0.300%, and the balance is Fe and impurities.
[0029] "C: 0.25%~0.70%" C is an important element for ensuring hardenability. If the C content is less than 0.25%, sufficient hardenability cannot be obtained, and it is difficult to ensure a tensile strength of 1600 MPa or more. Therefore, the C content is preferably 0.25% or more. The C content is preferably 0.28% or more. The tensile strength of the hot stamped member of this embodiment does not need to be limited to 1600 MPa or more, and the C content may be less than 0.25%. In this case, the lower limit of the C content may be 0.20%, 0.22%, or 0.24%. On the other hand, if the C content exceeds 0.70%, the strength of the hot stamped member becomes too high, and the limit hydrogen amount decreases significantly. Therefore, the C content is preferably 0.70% or less. The C content is preferably 0.55% or less, 0.50% or less, 0.45% or less, 0.40% or less, 0.36% or less, or 0.32% or less.
[0030] "Si: 0.005% to 1.000%" Si is an element contained to ensure hardenability. If the Si content is less than 0.005%, it is difficult to ensure a tensile strength of 1600 MPa or more. Therefore, the Si content is preferably 0.005% or more. More preferably, the Si content is 0.100% or more or 0.150% or more. Since the above effect is saturated even if more than 1.000% of Si is contained, the Si content is 1.000% or less. The Si content is preferably 0.500% or less. It is not necessary to limit the tensile strength of the hot stamped member of this embodiment to 1600 MPa or more, and the Si content may be less than 0.005%. In this case, the lower limit of the Si content may be 0.002% or 0.004%.
[0031] "Mn: 0.30%~3.00%" Mn is an element that contributes to improving the strength of a hot stamped member by solid solution strengthening. If the Mn content is less than 0.30%, the solid solution strengthening ability is poor, the martensite becomes soft, and the tensile strength decreases. Therefore, in order to obtain a tensile strength of 1600 MPa or more, the Mn content is preferably 0.30% or more. It is not necessary to limit the tensile strength of the hot stamped member of this embodiment to 1600 MPa or more, and the Mn content may be less than 0.30%. In this case, the lower limit of the Mn content may be 0.20%, 0.24%, or 0.27%. The Mn content is more preferably 0.40% or more, 0.50% or more, 0.60% or more, or 0.80% or more. On the other hand, if the Mn content exceeds 3.00%, coarse inclusions are generated in the steel, making it easier to cause fracture, and the hydrogen embrittlement resistance of the hot stamped member decreases, so the Mn content is set to 3.00% or less. The Mn content is preferably 2.50% or less or 2.00% or less, more preferably 1.80% or less, 1.60% or less, 1.40% or less, 1.20% or less, or 1.00% or less.
[0032] "P: 0.100% or less" P is an impurity element that segregates at grain boundaries and reduces the strength of the grain boundaries. If the P content exceeds 0.100%, the strength of the grain boundaries is significantly reduced, and the hydrogen embrittlement resistance of the hot stamped member is reduced. Therefore, the P content is preferably 0.100% or less. The P content is more preferably 0.050% or less, 0.030% or less, or 0.015% or less. The P content is further more preferably 0.010% or less, or 0.005% or less. There is no particular lower limit for the P content. Therefore, the lower limit for the P content is 0%. If the P content is reduced to less than 0.0005%, the dephosphorization cost increases significantly, which is economically undesirable, so the lower limit may be 0.0005% or 0.001% in practical operation.
[0033] "S: 0.1000% or less" S is an impurity element that forms inclusions in steel. If the S content exceeds 0.1000%, a large amount of inclusions will be generated in the steel, and the hydrogen embrittlement resistance of the hot stamped member will decrease. Therefore, the S content is preferably 0.1000% or less. The S content is more preferably 0.0300% or less, 0.0100% or less, 0.0070% or less, or 0.0050% or less. There is no particular lower limit for the S content. Therefore, the lower limit for the S content is 0%. If the S content is reduced to less than 0.00015%, the desulfurization cost will increase significantly, which is economically undesirable, so in practical operation, the lower limit may be 0.00015% or 0.0005%. The S content may be 0.0010% or more, or 0.0050% or more.
[0034] "N: 0.0100% or less" N is an impurity element that forms nitrides in steel and deteriorates the toughness and hydrogen embrittlement resistance of hot stamped members. If the N content exceeds 0.0100%, coarse nitrides are formed in the steel, and the hydrogen embrittlement resistance of the hot stamped members is significantly reduced. Therefore, the N content is set to 0.0100% or less. The N content is preferably 0.0050% or less. There is no particular lower limit for the N content. Therefore, the lower limit for the N content is 0%. If the N content is reduced to less than 0.0015%, the cost of denitrification increases significantly, which is economically undesirable, so the lower limit may be set to 0.0015% or 0.0020% in practical operation.
[0035] The base steel sheet constituting the hot stamping steel sheet 10 according to the present embodiment may contain, instead of a part of Fe, optional elements such as Cu: 0.01 to 1.00%, Ni: 0.01 to 1.00%, Cr: 0.001 to 1.000%, Mo: 0.001 to 1.000%, Nb: 0.001 to 0.200%, V: 0.01 to 1.00%, Ti: 0.001 to 0.150%, B: 0.001 to 0.0100%, Co: 0.01 to 1.00%, W: 0.01 to 1.00%, Sn: 0.01 to 1.00%, Sb: 0.01 to 1.00%, Zr: 0.01 to 1.00%, Mg: 0.001 to 0.150%, Al: 0.0010 to 1.0000%, It may contain one or more selected from the group consisting of Ca: 0.001 to 0.010% and REM: 0.001 to 0.300%. When the following optional elements are not contained, the content is 0%.
[0036] "Cu: 0%~1.00%" Cu diffuses into the plating layer of the hot stamped member during hot stamping and has the effect of reducing hydrogen that penetrates during heating in the manufacture of the hot stamped member, so it may be contained as necessary. Cu is also an effective element for improving the hardenability of steel and stably ensuring the strength of the coated steel member after quenching. When Cu is contained, in order to ensure the above-mentioned effects, the Cu content is preferably 0.01% or more. The Cu content is more preferably 0.10% or more. The Cu content is further preferably 0.15% or more. On the other hand, since the above-mentioned effects are saturated even if Cu is contained in an amount exceeding 1.00%, the Cu content is preferably 1.00% or less. The Cu content is more preferably 0.350% or less.
[0037] "Ni: 0%~1.00%" Ni may be contained since it is an important element for suppressing hot embrittlement caused by Cu during the manufacture of the base steel sheet and ensuring stable production. If the Ni content is less than 0.01%, the above effects may not be sufficiently obtained. Therefore, the Ni content is preferably 0.01% or more. The Ni content is preferably 0.05% or more. More preferably, the Ni content is 0.10% or more. On the other hand, if the Ni content exceeds 1.00%, the limit hydrogen content of the coated steel member decreases. Therefore, the Ni content is preferably 1.00% or less. The Ni content is preferably 0.50% or less or 0.25% or less. More preferably, the Ni content is 0.20% or less.
[0038] "Cr:0%~1.000%" Cr is an element that contributes to improving the strength of hot stamped members by solid solution strengthening, and may be contained as necessary. When Cr is contained, in order to ensure the above effects, the Cr content is preferably 0.001% or more. The Cr content is more preferably 0.050% or more. The Cr content is further preferably 0.100% or more. On the other hand, since the above effects are saturated even if the Cr content exceeds 1.000%, the Cr content is preferably 1.000% or less. The Cr content is more preferably 0.800% or less, 0.500% or less, or 0.250% or less.
[0039] "Mo:0%~1.000%" Mo is an element that contributes to improving the strength of hot stamped members by solid solution strengthening, and may be contained as necessary. When Mo is contained, in order to ensure the above effects, the Mo content is preferably 0.001% or more. The Mo content is more preferably 0.005% or more. The Mo content is further preferably 0.010% or more. In particular, the Mo content is preferably 0.100% or more. On the other hand, since the above effects are saturated even if Mo is contained in an amount exceeding 1.000%, the Mo content is preferably 1.000% or less. The Mo content is more preferably 0.800% or less, 0.500% or less, or 0.250% or less.
[0040] "Nb: 0%~0.200%" Nb is an element that contributes to improving the strength of hot stamped members by solid solution strengthening, and may be contained as necessary. When Nb is contained, in order to ensure the above effects, the Nb content is preferably 0.001% or more. The Nb content is more preferably 0.010% or more. The Nb content is further preferably 0.030% or more. On the other hand, since the above effects are saturated even if the Nb content exceeds 0.200%, the Nb content is preferably 0.200% or less. The Nb content is more preferably 0.100% or less.
[0041] "V:0~1.00%" V is an element that forms fine carbides and improves the limit hydrogen content of the hot stamped member due to its grain refining effect and hydrogen trapping effect. Therefore, V may be contained. In order to obtain the above effect, it is preferable to contain V in an amount of 0.01% or more, and more preferably 0.10% or more. However, if the V content exceeds 1.00%, the above effects are saturated and the economic efficiency decreases. Therefore, when V is contained, the V content is preferably 1.00% or less. The V content is more preferably 0.700% or less, 0.400% or less, or 0.250% or less.
[0042] "Ti: 0%~0.150%" Ti is an element that contributes to improving the strength of hot stamped members by solid solution strengthening, and may be contained as necessary. When Ti is contained, in order to ensure the above effects, the Ti content is preferably 0.001% or more. The Ti content is more preferably 0.010% or more. The Ti content is preferably 0.020% or more. On the other hand, even if Ti is contained in an amount exceeding 0.150%, the above effects are saturated, so the Ti content is preferably 0.150% or less. The Ti content is more preferably 0.100% or less, 0.060% or less, or 0.040% or less.
[0043] "B: 0%~0.0100%" Since B is an element that segregates at grain boundaries to improve the strength of the grain boundaries, it may be contained as necessary. When B is contained, in order to ensure the above-mentioned effects, the B content is preferably 0.0005% or more. The B content is more preferably 0.0005% or more. The B content is further preferably 0.0010% or more. On the other hand, since the above-mentioned effects are saturated even if the B content exceeds 0.0100%, the B content is preferably 0.0100% or less. The B content is more preferably 0.0075% or less, 0.0040% or less, or 0.0025% or less.
[0044] "Co: 0%~1.00%" Co is an element that has the effect of increasing the martensite start temperature (Ms point) and improves the toughness of the hot stamped member, so it may be contained as necessary. When Co is contained, in order to ensure the above effect, the Co content is preferably 0.01% or more. A more preferable Co content is 0.08% or more. On the other hand, if the Co content exceeds 1.00%, the hardenability of the steel decreases. Therefore, the Co content is preferably 1.00% or less. The Co content is more preferably 0.90% or less, 0.50% or less, or 0.10% or less.
[0045] "W:0%~1.00%" W is an element that enhances the hardenability of steel and enables the strength of hot stamped parts after hardening to be stably ensured. Therefore, it may be contained. W is also an element that improves corrosion resistance in a corrosive environment. In order to obtain the above effects, it is preferable to contain W at 0.01% or more. However, if the W content exceeds 1.00%, the above effects are saturated and the economic efficiency decreases. Therefore, if W is contained, the W content is preferably 1.00% or less. The W content is more preferably 0.75% or less, 0.40% or less, or 0.10% or less.
[0046] "Sn: 0%~1.00%" Sn is an element that improves corrosion resistance in a corrosive environment. Therefore, Sn may be contained. In order to obtain the above effects, it is preferable to contain Sn in an amount of 0.01% or more. However, if the Sn content exceeds 1.00%, the grain boundary strength decreases, and the limiting hydrogen content of the coated steel member after quenching decreases. Therefore, when Sn is contained, the Sn content is preferably 1.00% or less. The Sn content is more preferably 0.60% or less, 0.10% or less, or 0.05% or less.
[0047] "Sb: 0%~1.00%" Sb is an element that improves corrosion resistance in a corrosive environment. Therefore, Sb may be contained. In order to obtain the above effects, the Sb content is preferably 0.01% or more. However, if the Sb content exceeds 1.00%, the grain boundary strength decreases, and the limit hydrogen content of the hot stamped member after quenching decreases. Therefore, if Sb is contained, the Sb content is preferably 1.00% or less. The Sb content is more preferably 0.60% or less, 0.10% or less, or 0.05% or less.
[0048] "Zr: 0%~1.00%" Zr is an element that improves corrosion resistance in a corrosive environment. Therefore, it may be contained. In order to obtain the above effects, the Zr content is preferably 0.01% or more. However, if the Zr content exceeds 1.00%, the grain boundary strength decreases, and the limit hydrogen content of the hot stamped part after quenching decreases. Therefore, if Zr is contained, the Zr content is preferably 1.00% or less. The Zr content is more preferably 0.60% or less, 0.20% or less, or 0.05% or less.
[0049] "Mg: 0%~0.150%" Mg is an element that has the effect of deoxidizing molten steel to improve the soundness of the steel, and improves the toughness of the hot stamped member. Therefore, Mg may be contained as necessary. In order to reliably obtain the above effect, the Mg content is preferably 0.001% or more, and more preferably 0.008% or more. On the other hand, if the Mg content exceeds 0.150%, the above effect saturates and causes an increase in costs. Therefore, the Mg content is preferably 0.150% or less, and more preferably 0.100% or less, 0.050% or less, or 0.010% or less.
[0050] "Al: 0%~1.0000%" Al is an element that is generally used as a deoxidizer for steel. Therefore, Al may be contained. In order to obtain the above effects, it is preferable that the Al content is 0.0010% or more. The Al content is more preferably 0.0100% or more. However, if the Al content exceeds 1.0000%, the above effects are saturated and the economic efficiency decreases. Therefore, when Al is contained, the Al content is set to 1.0000% or less. The preferred Al content is 0.5000% or less, 0.1000% or less, 0.0500% or less, or 0.0300% or less.
[0051] "Ca: 0%~0.010%" Ca is an element that has the effect of deoxidizing molten steel and improving the soundness of the steel. In order to ensure this effect, the Ca content is preferably 0.001% or more. On the other hand, since the above effect saturates even if the Ca content exceeds 0.010%, the Ca content is preferably 0.010% or less. The Ca content is more preferably 0.007% or less, 0.005% or less, or 0.003% or less.
[0052] "REM: 0%~0.300%" Like Ca, REM is an element that has the effect of refining inclusions in steel and improving the limit hydrogen content of the coated steel member after quenching. In order to ensure this effect, the REM content is preferably 0.001% or more. On the other hand, even if the REM content exceeds 0.300%, the above effect saturates, so the REM content is preferably 0.300% or less. The REM content is more preferably 0.100% or less, 0.050% or less, 0.010% or less, or 0.005% or less. In this embodiment, REM refers to a total of 17 elements consisting of Sc, Y and lanthanoids, and the content of REM refers to the total content of these elements.
[0053] "Balance: Fe and impurities" The balance of the chemical composition of the base steel sheet 1 constituting the steel sheet for hot stamping 10 according to this embodiment is Fe and impurities. The impurities are those inevitably mixed in from steel raw materials or scrap and / or during the steelmaking process, or those intentionally added, and are permissible within a range that does not impair the properties of the hot stamped member after the steel sheet for hot stamping 10 according to this embodiment is hot stamped.
[0054] The chemical composition of the above-mentioned base steel sheet 1 may be measured by a general analytical method. For example, it may be measured using ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry). C and S may be measured using a combustion-infrared absorption method, and N may be measured using an inert gas fusion-thermal conductivity method. The surface plating layer may be removed by mechanical grinding before analyzing the chemical composition.
[0055] "Metal structure" Next, the metal structure of the base steel plate 1 constituting the steel plate 10 for hot stamping according to this embodiment will be described. The metal structure of the base steel plate 1 of the steel plate 10 for hot stamping is not limited, but in terms of area ratio in the cross section, it may be ferrite: 20-80%, pearlite: 20-80%, and the balance being one or more of bainite, martensite, and retained austenite. The area ratio of the balance may be less than 5%.
[0056] (Method for measuring the area ratio of ferrite and pearlite) The area ratios of ferrite and pearlite are measured by the following method. A cross section parallel to the rolling direction at the center position in the sheet width direction is mirror-finished and polished for 8 minutes at room temperature using colloidal silica that does not contain an alkaline solution to remove strain introduced into the surface layer of the sample. At any position in the longitudinal direction of the sample cross section, a region 50 μm long and from 1 / 8 of the sheet thickness depth to 3 / 8 of the sheet thickness depth from the surface is measured at measurement intervals of 0.1 μm using electron backscatter diffraction to obtain crystal orientation information so that a depth of 1 / 4 of the sheet thickness from the surface can be analyzed. For the measurement, a device consisting of a thermal field emission scanning electron microscope (JEOL JSM-7001F) and an EBSP detector (TSL DVC5 type detector) is used. At this time, the degree of vacuum inside the device is 9.6×10 -5 The exposure conditions are as follows: 1. The exposure time is 100 s, the exposure voltage is 15 kV, the exposure current level is 13, and the electron beam exposure level is 62. Furthermore, a backscattered electron image is taken in the same field of view. First, the crystal grains in which ferrite and cementite are precipitated in layers are identified from the backscattered electron image, and the area ratio of the crystal grains is calculated to obtain the area ratio of pearlite. After that, for the crystal grains other than those determined to be pearlite, the obtained crystal orientation information is used to determine the areas with a Grain Average Misorientation value of 1.0° or less as ferrite using the "Grain Average Misorientation" function installed in the software "OIM Analysis (registered trademark)" attached to the EBSP analysis device. The area ratio of the areas determined to be ferrite is obtained by calculating the area ratio of the ferrite.
[0057] (Method for measuring area ratio of bainite, martensite and retained austenite) In this embodiment, the total area ratio of bainite, martensite, and retained austenite is a value obtained by subtracting the area ratios of ferrite and pearlite from 100%.
[0058] The thickness of the base steel plate 1 of the hot stamping steel plate 10 according to this embodiment is not particularly limited, but from the viewpoint of reducing the weight of the vehicle body, it is preferably 0.5 to 3.5 mm. The thickness of the base steel plate 1 is preferably 0.8 mm or more, 1.0 mm or more, or 1.2 mm or more. The thickness of the base steel plate 1 is preferably 3.2 mm or less, 2.8 mm or less, or 2.4 mm or less.
[0059] (Al-Si alloy plating layer) The Al-Si alloy plating layer 2 of the hot stamping steel sheet 10 according to this embodiment is provided as an upper layer of the base steel sheet 1. The Al-Si alloy plating layer 2 is a plating containing Al and Si as main components. Here, containing Al and Si as main components means that the Al content is at least 3 mass% or more and the sum of the Al content and the Si content is 95 mass% or more. That is, the Al-Si alloy plating layer 2 has an Al content of 75 mass% or more, a Si content of 3 mass% or more, and the sum of the Al content and the Si content is 95 mass% or more. The Al content in the Al-Si alloy plating layer 2 is 75 to 97 mass% or less, and if the Al content in the Al-Si alloy plating layer 2 is in this range, a scale with good adhesion is formed on the surface of the base steel sheet during hot stamping. The Al content in the Al-Si alloy plating layer 2 is preferably 95 mass% or less or 93 mass% or less. The Al content in the Al-Si alloy plating layer 2 may be 91 mass % or less, or 88% or less, or 78% or more, 81% or more, or 85% or more.
[0060] The Si content in the Al-Si alloy plating layer 2 is preferably 3% by mass or more or 5% by mass or more. More preferably, the Si content in the Al-Si alloy plating layer 2 is 7% by mass or more or 9% by mass or more. The Si content in the Al-Si alloy plating layer 2 is preferably 20% by mass or less. More preferably, the Si content is 15% by mass or less or 12% by mass or less. If the Si content in the Al-Si alloy plating layer 2 is 3% by mass or more, the alloying of Fe-Al can be suppressed. Also, if the Si content in the Al-Si alloy plating layer 2 is 20% by mass or less, the increase in the melting point of the Al-Si alloy plating layer 2 can be suppressed, and the temperature of the hot-dip plating bath can be lowered. Therefore, if the Si content in the Al-Si alloy plating layer 2 is 20% by mass or less, the production cost can be reduced. The balance in the Al-Si alloy plating layer 2 is Fe and impurities. Examples of impurities include components that are inevitably mixed during the production of the Al-Si alloy plating layer 2 and components in the mother steel sheet 1.
[0061] The thickness (average layer thickness) of the Al-Si alloy plating layer 2 of the hot stamping steel sheet 10 according to this embodiment is 5 μm or more. More preferably, the thickness of the Al-Si alloy plating layer 2 is 8 μm or more, 12 μm or more, or 15 μm or more. If the thickness of the Al-Si alloy plating layer 2 is less than 5 μm, a scale with good adhesion cannot be formed during hot stamping. The thickness of the Al-Si alloy plating layer 2 is 50 μm or less. More preferably, the thickness of the Al-Si alloy plating layer 2 is 45 μm or less, 40 μm or less, or 35 μm or less. If the thickness of the Al-Si alloy plating layer 2 exceeds 50 μm, the above effects are saturated and the cost becomes high.
[0062] The thickness of the Al-Si alloy plating layer 2 is measured as follows. After cutting the hot stamping steel sheet 10 in the sheet thickness direction, the cross section of the hot stamping steel sheet 10 is polished. The polished cross section of the hot stamping steel sheet 10 is linearly analyzed from the surface of the hot stamping steel sheet 10 to the base steel sheet 1 using the ZAF method with an electron probe microanalyser (FE-EPMA), and the Al concentration and Si concentration in the detected components are measured. The measurement conditions may be an acceleration voltage of 15 kV, a beam diameter of about 100 nm, an irradiation time per point of 1000 ms, and a measurement pitch of 60 nm. A region in which the Si concentration is 3 mass% or more and the sum of the Al concentration and the Si concentration is 95 mass% or more is determined to be the Al-Si alloy plating layer 2. The thickness of the Al-Si alloy plating layer 2 is the length in the sheet thickness direction of the above region. The thickness of the Al-Si alloy plating layer 2 is measured at five positions spaced apart by 5 μm, and the arithmetic average of the values obtained is taken as the thickness of the Al-Si alloy plating layer 2.
[0063] The Al content and Si content in the Al-Si alloy plating layer 2 in the hot stamping steel sheet 10 are obtained by taking a test piece and measuring the Al content and Si content at a position halfway through the total thickness of the Al-Si alloy plating layer 2 according to the test method described in JIS K 0150 (2009).
[0064] (Al oxide film) The aluminum oxide coating 3 of the steel sheet 10 for hot stamping according to this embodiment is provided as an upper layer of the Al-Si alloy plating layer 2 in contact with the Al-Si alloy plating layer 2. The aluminum oxide coating is a region having an O content of 20 atomic % or more. The aluminum oxide coating may be omitted. The thickness of the aluminum oxide coating is 0 to 20 nm. The thickness (average film thickness) of the aluminum oxide coating 3 of the hot stamping steel sheet 10 according to this embodiment is 20 nm or less. Preferably, the thickness of the aluminum oxide coating 3 is 10 nm or less. If the thickness of the aluminum oxide coating 3 of the hot stamping steel sheet 10 exceeds 20 nm, the coverage of the surface plating layer 4 provided as an upper layer of the aluminum oxide coating 3 becomes less than 90%, and hydrogen embrittlement resistance may deteriorate. Since the aluminum oxide coating 3 is not necessary, the lower limit of the aluminum oxide coating 3 is 0 nm. In that case, the surface plating layer 4 is formed so as to be in contact with the Al-Si alloy plating layer 2. The thickness of the aluminum oxide coating 3 may be 2 nm or more.
[0065] The thickness of the aluminum oxide coating 3 is evaluated by alternately repeating Ar sputtering and X-ray photoelectron spectroscopy (XPS) measurement. Specifically, the hot stamping steel sheet 10 is sputtered by Ar sputtering (accelerating voltage 20 kV, sputter rate 1.0 nm / min), and then XPS measurement is performed. The Ar sputtering and XPS measurement are alternately performed, and these measurements are repeated until a peak of binding energy of 73.8 eV to 74.5 eV of the oxidized Al 2p orbital appears in the XPS measurement and disappears. The average film thickness of the aluminum oxide coating 3 is calculated from the sputtering time and sputtering rate from the position where the O content becomes 20 atomic% or more for the first time after the start of sputtering to the position where the O content becomes less than 20 atomic%. The sputtering rate is calculated in terms of SiO2. The thickness of the aluminum oxide coating 3 is the arithmetic average value measured at two points.
[0066] (surface plating layer) The surface plating layer 4 of the hot stamping steel sheet 10 according to this embodiment is provided in contact with the Al oxide coating 3 as an upper layer of the Al oxide coating 3. When the Al oxide coating 3 is not provided, the surface plating layer 4 is provided in direct contact with the Al-Si alloy plating layer 2 as an upper layer of the Al-Si alloy plating layer 2. The surface plating layer 4 is an alloy plating made of two or more of Zn, Sn, and Ni, or an Sn plating. The surface plating layer 4 has a total of Sn content, Ni content, and Zn content of more than 90 mass%, an Sn content of 10 mass% or more, an Ni content of less than 90 mass%, and a Zn content of less than 50 mass%. When the chemical composition of the surface plating layer 4 is within the above range, the elements and oxides constituting the surface plating layer are unlikely to cause a reduction reaction of hydrogen, and even if hydrogen atoms are generated and adsorbed on the surface, the Tafel reaction in which hydrogen atoms bond with each other and become hydrogen gas and are released is promoted, so that hydrogen is unlikely to penetrate into the base steel sheet. Therefore, by forming the surface plating layer 4, it is possible to suppress the amount of hydrogen that penetrates into the steel sheet 10 for hot stamping during hot stamping. For this reason, the surface plating layer 4 can also be called a hydrogen penetration prevention layer.
[0067] In order to reduce the amount of hydrogen penetration in the hot stamped member, the total of the Sn, Ni and Zn contents of the surface plating layer 4 is more than 90 mass%. The total of the Sn, Ni and Zn contents of the surface plating layer 4 may be 92 mass% or more, 94 mass% or more, 96 mass% or more, or 98 mass% or more, or may be 100 mass%. On the other hand, the total of the Sn, Ni and Zn contents of the surface plating layer 4 may be 98 mass% or less, 96 mass% or less, or 94 mass% or less.
[0068] In order to suppress the amount of hydrogen penetration into the hot stamped member, the Sn content of the surface plating layer 4 is 10 mass% or more. The Sn content of the surface plating layer 4 may be 12 mass% or more, 14 mass% or more, 16 mass% or more, 18 mass% or more, 20 mass% or more, 30 mass% or more, 40 mass% or more, 60 mass% or more, 80 mass% or more, 90 mass% or more, 94 mass% or more, 96 mass% or more, or 98 mass% or more. In particular, the Sn content of the surface plating layer 4 may be 100 mass%. That is, the surface plating layer 4 may be 100% Sn plating. On the other hand, the Sn content of the surface plating layer 4 may be 98 mass% or less, 96 mass% or less, 94 mass% or less, 90 mass% or less, 85 mass% or less, 80 mass% or less, 60 mass% or less, 50 mass% or less, 30 mass% or less, or 20 mass% or less.
[0069] In order to reduce the amount of hydrogen penetration in the hot stamped member, the Ni content of the surface plating layer 4 is less than 90 mass%. The Ni content of the surface plating layer 4 may be 85 mass% or less, 80 mass% or less, 60 mass% or less, 40 mass% or less, 20 mass% or less, 10 mass% or more, 8 mass% or less, 6 mass% or less, 4 mass% or less, or 2 mass% or less, or 0 mass%. On the other hand, the Ni content of the surface plating layer 4 may be 2 mass% or more, 4 mass% or more, 6 mass% or more, 8 mass% or more, 10 mass% or more, 20 mass% or more, 40 mass% or more, 60 mass% or more, 80 mass% or more, or 85 mass% or more.
[0070] In order to reduce the amount of hydrogen penetration in the hot stamped member, the Zn content of the surface plating layer 4 is less than 50 mass%. The Zn content of the surface plating layer 4 may be 48 mass% or less, 46 mass% or less, 44 mass% or less, 40 mass% or less, 30 mass% or less, 20 mass% or less, 10 mass% or more, 8 mass% or less, 6 mass% or less, 4 mass% or less, 2 mass% or less, or 0 mass%. On the other hand, the Zn content of the surface plating layer 4 may be 1 mass% or more, 2 mass% or more, 4 mass% or more, 6 mass% or more, 8 mass% or more, 10 mass% or more, 15 mass% or more, 20 mass% or more, or 30 mass% or more.
[0071] The surface plating layer 4 may contain elements (including impurities) other than Sn, Zn and Ni, so long as the total content of Sn, Ni and Zn in the surface plating layer 4 exceeds 90 mass%. The total content of elements other than Sn, Zn and Ni is 10% or less. The total content of elements other than Sn, Ni and Zn may be 5 mass% or less, 3 mass% or less, or 1 mass% or less.
[0072] The thickness of the surface plating layer 4 according to this embodiment is more than 300 nm. If the thickness of the surface plating layer 4 is 300 nm or less, the penetration of hydrogen into the base steel sheet 1 during hot stamping cannot be sufficiently suppressed. A more preferable thickness of the surface plating layer 4 is 400 nm or more or 500 nm or more. Furthermore, if the thickness of the surface plating layer 4 exceeds 2500 nm, the effect of suppressing the amount of hydrogen penetrating into the base steel sheet 1 becomes saturated, resulting in high costs. For this reason, the thickness of the surface plating layer 4 is 2500 nm or less. A preferable thickness of the surface plating layer 4 is 2000 nm or less, 1500 nm or less, or 1000 nm or less, and more preferably 730 nm or less.
[0073] It is preferable that the coverage of the surface plating layer 4 with respect to the Al oxide coating 3 (if the Al oxide coating 3 is not present, the coverage of the surface plating layer 4 with respect to the Al-Si alloy plating layer 2) is 90% or more. More preferably, the coverage of the surface plating layer 4 is 95% or more. If the coverage of the surface plating layer 4 is less than 90%, the reaction between water vapor and Al on the surface of the Al-Si alloy plating layer 2 during hot stamping may not be sufficiently suppressed. The coverage of the surface plating layer 4 may be 100% or less, or may be 99% or less.
[0074] The coverage of the surface plating layer 4 is evaluated by XPS measurement. Specifically, the XPS measurement is performed using a Quantum2000 model manufactured by ULVAC-PHI, Inc., with Al Kα radiation as the radiation source, with an output of 15 kV, 25 W, a spot size of 100 μm, 10 scans, and the hot stamping steel sheet 10 is scanned over the entire energy range, and analyzed using analysis software MultiPak V.8.0 manufactured by ULVAC-PHI, Inc., to obtain the Sn content (atomic%), Zn content (atomic%), Ni content (atomic%), Al content (atomic%), and other component contents (atomic%) in the detected metal components. The obtained contents (atomic%) can be converted to contents (mass%) to obtain the Sn content (mass%), Zn content (mass%), Ni content (mass%), and Al content (mass%). The ratio (%) of the total content of Sn content (mass%), Zn content (mass%), and Ni content (mass%) to the sum of the Sn content (mass%), Zn content (mass%), Ni content (mass%), and Al content (mass%) is calculated, and the obtained ratio is regarded as the coverage rate.
[0075] The thickness of the surface plating layer 4 can be measured by glow discharge optical emission spectrometry (GDS). The discharge conditions are 35 W (constant power mode), Ar pressure during measurement is 600 Pa, and the discharge range is 4 mmφ. The distance between the electrodes is 0.15 mm to 0.25 mm, and a high frequency, direct glow, high frequency glow, etc. may be selected and applied from the back of the sample to measure. The discharge voltage may be 30 W to 50 W (constant power mode), and the Ar pressure during measurement may be 500 Pa to 700 Pa. The discharge range may be 2 mmφ to 6 mmφ. The measurement time at one point may be the time (α) until 90% or more of Fe is detected, and then the time (α×0.2) of about 20% of that time may be further measured (total α+0.2α). The thickness of the surface plating layer 4 can be obtained by measuring the area where Al is detected from the outermost surface of the hot stamping steel sheet 10 and the total of the plating components (Sn, Zn, Ni) of the surface plating layer becomes 50%. The thickness (nm) of the surface plating layer 4 is determined as follows. First, the depth cut per unit time is calculated from the depth cut from the start to the end of the measurement (until Al is detected and the total of the plating components (Sn, Zn, Ni) of the surface plating layer is 50%) and the measurement time. Next, the thickness of the surface plating layer 4 of the hot stamping steel sheet 10 is calculated by multiplying the depth cut per unit time obtained by the measurement time.
[0076] The contents of Zn, Sn, and Ni in the surface plating layer 4 are defined as the concentrations of each element at the center position in the sheet thickness direction of the surface plating layer 4 obtained by measuring the thickness of the surface plating layer 4 described above.
[0077] <Hot stamping parts> Next, the hot stamped member according to this embodiment is obtained by hot stamping the steel sheet 10 for hot stamping. When the steel sheet 10 for hot stamping contains Cu in the base steel, Cu may be diffused to the surface of the hot stamped member. The components (Sn, Zn, Ni) of the surface plating layer and their oxides (hydroxides) may remain on the surface of the hot stamped member according to this embodiment. Hereinafter, the hot stamped member obtained by hot stamping the steel sheet 10 for hot stamping according to this embodiment will be described. The hot stamped member according to this embodiment includes a base steel and a plating layer provided on the base steel.
[0078] (base steel) The base material (base steel) has the same chemical composition as the base steel sheet 1 of the hot stamping steel sheet 10. The chemical composition of the base steel can be measured by the method described above.
[0079] (Plating layer) The plating layer of the hot stamped member has, from the surface of the plating layer, a surface rich region in which the sum of the Sn content, the Zn content, and the Ni content is 50 mass% or more, the Sn content is 7 mass% or more, the Ni content is less than 72 mass%, and the Zn content is less than 40 mass%, an Al rich region in which the sum of the Sn content, the Zn content, and the Ni content is less than 50 mass%, the Al content is 10 mass% or more, and the Fe content is 50 mass% or less, and an Fe rich region in which the Al content is 10 mass% or more and the Fe content exceeds 50 mass%, in this order. Note that the Ni content of the surface rich region may be less than 50 mass%.
[0080] Hereinafter, the plating layer will be described using as an example a hot stamped member obtained by hot stamping a steel sheet 10 for hot stamping in which the surface plating layer 4 is 100% Sn plated. The structure of the plating layer of the hot stamped member according to this embodiment will be described with reference to FIG. 3. FIG. 3 is a depth profile of the plating layer of the hot stamped member. The vertical axis of FIG. 3 indicates the content of each element, and the horizontal axis indicates the depth from the outermost surface of the hot stamped member (outermost surface: 0 μm). The solid line indicates the Fe content, the dashed line indicates the Al content, and the dotted line indicates the Sn content. Here, for convenience, the explanation will be based on FIG. 3 in which the surface plating layer is 100% Sn plated, but if the surface plating layer 4 is not 100% Sn plated, in the following explanation, it will be easier to understand if the "Sn content" is replaced with the "total of the Sn content, the Ni content, and the Zn content". For this reason, "(Note 1)" is added to the "Sn content" which can be replaced with the "total of the Sn content, the Ni content, and the Zn content".
[0081] When the steel sheet 10 for hot stamping has a surface plating with an Sn content of 100%, the Sn content (Note 1) of the plating layer of the hot stamping component is 50% by mass or more, the Sn content is 7% by mass or more (Note 2: Since the Sn content is 50% by mass or more, it is natural that the Sn content is 5% by mass or more. However, this requirement is also stated just to be sure so that the case other than the surface plating with an Sn content of 100% is easy to understand.), the Ni content is less than 90% by mass, and the Zn content is less than 40% by mass. (Note 3: When the steel sheet 10 for hot stamping has a surface plating with an Sn content other than 100%, the surface rich region is an Sn-rich region where the Ni content is less than 90% by mass and the Zn content is less than 40% by mass.) This is region A in Figure 3. The Al-rich region where the Sn content (Note 1) is less than 50 mass%, the Al content is 10 mass% or more, and the Fe content is 50 mass% or less is region B in Figure 3. The Fe-rich region where the Al content is 10 mass% or more and the Fe content exceeds 50 mass% is region C in Figure 3. The presence of a plating layer having a surface rich region, an Al rich region, and an Fe rich region in this order from the outermost surface of the hot stamped member can suppress corrosion of the hot stamped member. The boundary position between the surface rich region and the Al rich layer of the hot stamped member, including cases other than when the surface plating layer of the hot stamping steel sheet 10 is 100% Sn plated, is substantially a position where the total of the Sn content, the Ni content, and the Zn content is 50 mass%. In other words, with respect to the requirement that the surface rich layer has an Sn content of 7 mass% or more, an Ni content of less than 72 mass%, and an Zn content of less than 40 mass%, the lower limit of the Sn content may be increased, or the upper limit of the Ni content may be decreased, or the upper limit of the Zn content may be decreased. For example, the lower limit of the Sn content of the surface rich region may be 8 mass%, 9 mass%, or 10 mass%. The upper limit of the Ni content of the surface rich region may be 70 mass%, 65 mass%, 60 mass%, 50 mass%, 40 mass%, 20 mass%, or 10 mass%. The upper limit of the Zn content in the surface rich region may be 45 mass %, 42 mass %, 40 mass %, 35 mass %, 30 mass %, 20 mass %, or 10 mass %. The thickness of the plating layer of the hot stamped component is calculated from the sum of the thicknesses of the surface rich region, the Al rich region, and the Fe rich region. In the following description, the content of each element that is not indicated as a maximum value or an average value is the content of each element at each depth position.
[0082] In the hot stamped member according to this embodiment, in the region from the surface of the plating layer to a position 100 nm in the thickness direction from the surface of the plating layer, the maximum sum of the Sn content, Ni content and Zn content is 50 mass% or more, and the Fe content is 10 mass% or less. In the hot stamped member according to this embodiment, in the region from a position 100 nm in the thickness direction from the surface of the plating layer to a position 500 nm in the thickness direction from the surface of the plating layer, the maximum sum of the Sn content, Ni content and Zn content is 5 mass% or more, and the Fe content is 40 mass% or less. In the hot stamped member according to this embodiment, in the region from a position 500 nm in the thickness direction from the surface of the plating layer to a position 1000 nm in the thickness direction from the surface of the plating layer, the maximum sum of the Sn content, Ni content and Zn content is 1 mass% or more, and the Fe content is 50 mass% or less.
[0083] Hereinafter, a hot stamped member obtained by hot stamping a steel sheet 10 for hot stamping having a surface plating layer 4 formed by Sn plating (i.e., the total of Ni content and Zn content is 0 mass%) will be described as an example. The structure from the surface of the plating layer of the hot stamped member according to this embodiment to a position 1000 nm from the surface of the plating layer in the thickness direction will be described with reference to FIG. 4. The vertical axis of FIG. 4 indicates the content of each element, and the horizontal axis indicates the depth from the outermost surface of the hot stamped member (outermost surface: 0 μm). The solid line indicates the Fe content, the dashed line indicates the Al content, and the dotted line indicates the Sn content. Here, for convenience, the description will be based on FIG. 4 in which the surface plating layer is 100% Sn plating, but if the surface plating layer 4 is not 100% Sn plating, in the following description, it will be easier to understand if the "Sn content" is replaced with the "total of Sn content, Ni content, and Zn content". For this reason, "(Note 1)" is added to the "Sn content" which can be replaced with the "total of Sn content, Ni content, and Zn content".
[0084] The region from the surface of the plating layer of the hot stamped component according to this embodiment to a position 100 nm in the thickness direction from the surface of the plating layer is region D in Fig. 4. The region from a position 100 nm in the thickness direction from the surface of the plating layer of the hot stamped component to a position 500 nm in the thickness direction from the surface of the plating layer is region E in Fig. 4. The region from a position 500 nm in the thickness direction from the surface of the plating layer to a position 1000 nm in the thickness direction from the surface of the plating layer is region F in Fig. 4. Each region will be described below.
[0085] "The area from the surface of the plating layer to a position 100 nm from the surface of the plating layer in the thickness direction" In the region from the surface of the plating layer of the hot stamped component to a position 100 nm from the surface of the plating layer of the hot stamped component in the thickness direction, the maximum Sn content (Note 1) is 50 mass% or more, and the Fe content is 10 mass% or less. In the region from the surface of the plating layer to a position 100 nm from the surface of the plating layer in the thickness direction, the Al content may be 1 mass% or more.
[0086] If the maximum Sn content (Note 1) is less than 50 mass% in the region from the surface of the plating layer of the hot stamped component to a position 100 nm from the surface of the plating layer of the hot stamped component in the thickness direction, the Al content or Fe content of the outermost surface of the hot stamped component will be excessively high, and the amount of hydrogen penetration during hot stamping of the hot stamped component will decrease. For this reason, the maximum Sn content (Note 1) is 50 mass% or more. A more preferable maximum value of the Sn content (Note 1) is 70 mass% or more. The Sn content (Note 1) may be 90 mass% or less.
[0087] If the Fe content exceeds 10 mass% in the region from the surface of the plating layer of the hot stamped member to a position 100 nm from the surface of the plating layer of the hot stamped member in the thickness direction, Fe, which causes corrosion of the hot stamped member, becomes excessively large on the outermost surface of the hot stamped member (the surface of the plating layer of the hot stamped member), and the red rust resistance of the hot stamped member decreases. Therefore, the Fe content is 10 mass% or less. The Fe content is more preferably 5 mass% or less.
[0088] If the maximum Al content is less than 1 mass% in the region from the surface of the plating layer of the hot stamped member to a position 100 nm from the surface of the plating layer of the hot stamped member in the thickness direction, the adhesion (of oxides containing surface plating components, etc.) decreases, and the Sn oxide of the surface layer becomes more likely to peel off, which may cause indentations due to the peeled off material. Therefore, the maximum Al content is preferably 1 mass% or more. The maximum Al content is more preferably 5 mass% or more. The Al content may be 50 mass% or less.
[0089] "The region from 100 nm from the surface of the plating layer in the thickness direction to 500 nm from the surface of the plating layer in the thickness direction" In a region from a position 100 nm in the thickness direction from the surface of the plating layer of the hot stamped member to a position 500 nm in the thickness direction from the surface of the plating layer of the hot stamped member, the maximum Sn content (Note 1) is 5 mass% or more, and the Fe content is 40 mass% or less. Incidentally, even in cases where the surface plating layer 4 of the steel sheet 10 for hot stamping is other than 100% Sn plating, in addition to the maximum total value of the Sn content, Ni content, and Zn content being 5 mass% or more, the maximum Sn content may be 0.5 mass% or more or 1 mass% or more.
[0090] If the maximum Sn content (Note 1) is less than 5 mass% in the region from 100 nm in the thickness direction from the surface of the plating layer of the hot stamped component to 500 nm in the thickness direction from the surface of the plating layer of the hot stamped component, the adhesion (of oxides containing surface plating components, etc.) decreases, making the surface Sn oxide more likely to peel off, which may cause pressure scratches due to the peeled off material. Therefore, the maximum Sn content (Note 1) is 5 mass% or more. A more preferable maximum Sn content (Note 1) is 10 mass% or more.
[0091] When the Fe content exceeds 40 mass% in the region from 100 nm in the thickness direction from the surface of the plating layer of the hot stamped member to 500 nm in the thickness direction from the surface of the plating layer of the hot stamped member, the Fe content at the outermost surface of the hot stamped member becomes excessively high. Therefore, the Fe content is 40 mass% or less. The Fe content is more preferably 25 mass% or less.
[0092] The remainder in the region from 100 nm in the thickness direction from the surface of the plating layer of the hot stamped member to 500 nm in the thickness direction from the surface of the plating layer of the hot stamped member is Al, Si, and impurities. Examples of impurities include elements that are mixed in from steel raw materials or scrap and / or during the production process of the hot stamped member according to the present embodiment, or that are intentionally added, and are permissible within a range that does not impair the properties of the hot stamped member.
[0093] "The region from 500 nm from the surface of the plating layer in the thickness direction to 1000 nm from the surface of the plating layer in the thickness direction" In a region from a position 500 nm in the thickness direction from the surface of the plating layer of the hot stamped component to a position 1,000 nm in the thickness direction from the surface of the plating layer of the hot stamped component, the maximum Sn content (Note 1) is 1 mass% or more, and the Fe content is 50 mass% or less.
[0094] If the maximum Sn content (Note 1) is less than 1 mass% in the region from the surface of the plating layer of the hot stamped component to a position 500 nm in the thickness direction from the surface of the plating layer of the hot stamped component to a position 1000 nm in the thickness direction from the surface of the plating layer of the hot stamped component, alloying may not be sufficiently performed during heat treatment, and the adhesion of the plating of the surface layer may become insufficient. Therefore, the maximum Sn content (Note 1) is 1 mass% or more. A more preferable maximum value of the Sn content (Note 1) is 5 mass% or more. The maximum value of the Sn content (Note 1) may be 30 mass% or less.
[0095] When the Fe content exceeds 50 mass% in the region from 500 nm in the thickness direction from the surface of the plating layer of the hot stamped member to 1000 nm in the thickness direction from the surface of the plating layer of the hot stamped member, the Fe content of the outermost surface of the hot stamped member becomes excessively high. Therefore, the Fe content is 50 mass% or less. The Fe content is more preferably 40 mass% or less.
[0096] In the region from a position 500 nm from the surface of the plating layer of the hot stamped member in the thickness direction to a position 1000 nm from the surface of the plating layer of the hot stamped member in the thickness direction, the balance is Al, Si, and impurities. Examples of impurities include elements that are mixed in from steel raw materials or scrap and / or in the process of producing the hot stamped member according to the present embodiment, or that are intentionally added, and are permissible within a range that does not impair the properties of the hot stamped member.
[0097] The depth profile of each element in the plating layer of the hot stamped component can be measured by glow discharge optical emission spectrometry (GDS). The distance between the electrodes is 0.15mm to 0.25mm, and a high frequency, direct glow, high frequency glow, etc. may be applied to the back of the sample. The discharge voltage may be 30W to 50W (constant power mode), and the Ar pressure during measurement may be 500Pa to 700Pa. The discharge range may be 2mmφ to 6mmφ. The measurement time at one location may be measured as the time until 90% or more of Fe is detected (defined as α), and then a further measurement may be performed for about 20% of that time (α x 0.2) (total α + 0.2α). The depth profile of each element can be obtained by performing measurements from the outermost surface of the hot stamped component to the area where the Fe element of the base steel is stable. The depth (nm) from the surface of the plating layer is obtained as follows. First, the depth cut per unit time is calculated from the depth cut from the start to the end of the measurement and the measurement time. Next, the depth from the surface of the plating layer of the hot stamped component is calculated by multiplying the depth cut per unit time by the measurement time. If the surface of the hot stamped component is very uneven and vacuum drawing is not possible, an indium wire with a diameter of several hundred μm is pressed against the hot stamped component as a sealing material for measurement. A circle of the same size as the vacuum drawing part of the measurement area is surrounded by the indium wire, and the indium wire is pressed against the hot stamped component to fill in the surface unevenness, and then the GDS measurement is performed.
[0098] "At least one of Sn oxide, Sn hydroxide, Ni oxide, Ni hydroxide, Zn oxide, or Zn hydroxide on the surface of the plating layer" At least one of Sn oxide, Sn hydroxide, Ni oxide, Ni hydroxide, Zn oxide, and Zn hydroxide may be present in the region from the surface of the plating layer of the hot stamped member to a position 20 nm from the surface of the plating layer in the thickness direction. The presence of at least one of Sn oxide, Sn hydroxide, Ni oxide, Ni hydroxide, Zn oxide, and Zn hydroxide on the surface of the plating layer improves the chemical conversion property and electrodeposition paintability. Examples of Sn oxide include SnO, SnO2, and SnO3. Examples of Sn hydroxide include Sn(OH)2. Examples of Zn oxide include Zn(OH)2. Examples of Zn hydroxide include ZnO. Examples of Ni oxide include NiO or Ni2O3. Examples of Ni hydroxide include NiOH or Ni(OH)2.
[0099] "In the region from the surface of the plating layer to a position 20 nm from the surface of the plating layer in the thickness direction, the total content of Sn, Zn, and Ni is 30 mass% or more." In the region from the surface of the plating layer of the hot stamped member to a position 20 nm from the surface of the plating layer of the hot stamped member in the thickness direction, the total of the Sn content, the Zn content, and the Ni content is preferably 30 mass% or more. If the total of the Sn content, the Zn content, and the Ni content is 30 mass% or more, the amount of hydrogen penetration after hot stamping can be further suppressed. More preferably, the total of the Sn content, the Zn content, and the Ni content is 40 mass% or more.
[0100] The presence of Sn oxide, Sn hydroxide, Ni oxide, Ni hydroxide, Zn oxide, or Zn hydroxide can be confirmed by X-ray photoelectron spectroscopy (XPS). Specifically, the hot stamped part is sputtered and etched by Ar sputtering (accelerating voltage 20 kV, sputter rate 1.0 nm / min), and then XPS is measured. XPS is measured by scanning the outermost surface of the hot stamped part over the entire energy range using an ULVAC-PHI Quantum2000 with an Al Kα radiation source, output of 15 kV, 25 W, spot size of 100 μm, and 10 scans. The Ar sputtering etching and XPS measurements are alternately performed, and these measurements are repeated up to a position 20 nm from the plating layer in the thickness direction. The depth from the surface of the plating layer is calculated from the sputtering etching time and the sputtering rate. The sputtering etching rate is calculated in terms of SiO2. In the region from the surface of the plating layer of the hot stamped member to a position 20 nm from the surface of the plating layer in the thickness direction, if peaks are detected at 486.0 eV to 486.8 eV originating from the 2p orbital of Sn oxide or Sn hydroxide, 1021.7 eV to 1022.5 eV originating from the 2p orbital of Zn oxide or Zn hydroxide, and 854 eV to 857 eV originating from the 2p orbital of Ni oxide or Ni hydroxide, it is determined that at least one of Sn oxide, Sn hydroxide, Ni oxide, Ni hydroxide, Zn oxide, or Zn hydroxide is present in the region from the surface of the plating layer of the hot stamped member to a position 20 nm from the surface of the plating layer in the thickness direction. More specifically, the presence or absence of Sn oxide, Sn hydroxide, Ni oxide, Ni hydroxide, Zn oxide, or Zn hydroxide is measured by removing the sample after XPS measurement of the sample by the above method. Then, the background is removed from the measurement data of the sample. If a peak of 1000 c / s or more is detected in the portion corresponding to each oxide or hydroxide peak after background removal, it is determined that at least one of Sn oxide, Sn hydroxide, Ni oxide, Ni hydroxide, Zn oxide, or Zn hydroxide is present.The total Sn content, Zn content, and Ni content in the region from the surface of the plating layer of the hot stamped component to a position 20 nm from the surface of the plating layer in the thickness direction is calculated from all elements detected in the above-mentioned XPS measurement.
[0101] "Thickness of plating layer" The thickness of the plating layer of the hot stamped member is the total thickness of the surface rich region, the Al rich region, and the Fe rich region. If the thickness of the plating layer of the hot stamped member is less than 5 μm, sufficient corrosion resistance may not be obtained. Therefore, the thickness of the plating layer is preferably 5 μm or more. The thickness of the plating layer is more preferably 10 μm or more, 20 μm or more, or 30 μm or more. If the thickness of the plating layer exceeds 200 μm, the effect of improving the corrosion resistance is saturated. Therefore, the thickness of the plating layer is preferably 200 μm or less. The thickness of the plating layer may be 180 μm or less, 150 μm or less, 120 μm or less, or 100 μm or less.
[0102] The above describes the case where the hot stamped member is obtained by hot stamping the steel sheet for hot stamping 10 having the surface plating layer 4 plated with Sn. The thickness of the hot stamped member according to the present embodiment is not particularly limited, but is preferably 0.5 to 3.5 mm from the viewpoint of reducing the weight of the vehicle body. The thickness of the hot stamped member is preferably 0.8 mm or more, 1.0 mm or more, or 1.2 mm or more. The thickness of the hot stamped member is preferably 3.2 mm or less, 2.8 mm or less, or 2.4 mm or less. The tensile strength of the hot stamped member according to the present embodiment is not particularly limited, but may be 1150 MPa or more, 1300 MPa or more, 1500 MPa or more, 1600 MPa or more from the viewpoint of reducing the weight of the vehicle body. The tensile strength of the hot stamped member may be 2500 MPa or less, 2200 MPa or less, 2000 MPa or less, or 1800 MPa or less.
[0103] <Method of manufacturing steel sheets for hot stamping> Next, a suitable manufacturing method of the hot stamping steel sheet 10 will be described. The slab (steel material) to be subjected to hot rolling may be a slab manufactured by a conventional method, for example, a slab manufactured by a general method such as a continuous casting slab or a thin slab caster. The hot rolling may also be performed by a general method, and is not particularly limited. After hot rolling, the slab is coiled to obtain a mother steel sheet.
[0104] After coiling, cold rolling may be further performed as necessary. The cumulative reduction in cold rolling is not particularly limited, but is preferably 40 to 60% from the viewpoint of the shape stability of the base steel sheet.
[0105] "Al-Si alloy plating" The above hot-rolled steel sheet is directly or after cold rolling, and is then plated with an Al-Si alloy. The method for forming the Al-Si alloy plating layer 2 is not particularly limited, and hot-dip plating, electroplating, vacuum deposition, cladding, thermal spraying, etc. can be used. Hot-dip plating is particularly preferred.
[0106] When the Al-Si alloy plating layer 2 is formed by hot dip plating, the above-mentioned base steel sheet 1 is immersed in a plating bath whose components are adjusted so that the Si content is at least 3 mass% and the total of the Al content and the Si content is 95 mass% or more to obtain an Al-Si alloy plated steel sheet. The temperature of the plating bath is preferably in the range of 660°C to 690°C. Before forming the Al-Si alloy plating layer 2, the hot rolled steel sheet may be heated to a plating bath temperature of about 650°C to 780°C and then plated.
[0107] In addition, when hot-dip plating is performed, the plating bath may contain Fe as an impurity in addition to Al and Si. As long as the Si content is 3 mass% or more and the sum of the Al content and the Si content is 95 mass% or more, the plating bath may further contain Ni, Mg, Ti, Zn, Sb, Sn, Cu, Co, In, Bi, Ca, misch metal, etc.
[0108] "Aluminum oxide film removal" Before forming the surface plating layer 4, the aluminum oxide coating may be removed from the steel sheet (hereinafter, referred to as an aluminum-plated steel sheet) after the formation of the Al-Si alloy plating layer 2 to obtain an aluminum oxide coating-removed steel sheet. The aluminum oxide coating 3 is removed by immersing the aluminum-plated steel sheet in an acidic or basic removing solution. An example of an acidic removing solution is dilute hydrochloric acid (HCl 0.1 mol / L). An example of a basic removing solution is an aqueous sodium hydroxide solution (NaOH 0.1 mol / L). The immersion time is adjusted so that the aluminum oxide coating 3 after the formation of the surface plating layer 4 is 20 nm or less. For example, when the bath temperature is 40° C., the aluminum oxide coating is removed by immersing for 1 minute.
[0109] "Surface plating layer" After the formation of the Al-Si alloy plating, or after removing the aluminum oxide coating 3 so that the average thickness of the aluminum oxide coating 3 after the formation of the surface plating layer 4 is 20 nm or less, it is preferable to obtain a steel sheet for hot stamping by subjecting the steel sheet from which the aluminum oxide coating has been removed to Sn plating, Sn-Ni plating, Sn-Zn plating, Sn-Ni-Zn plating, or the like within 1 minute to form the surface plating layer 4. The surface plating layer 4 may be formed by electroplating, vacuum deposition, or the like.
[0110] When the surface plating layer 4 is Sn plating, for example, the steel sheet after the formation of the Al-Si alloy plating or after the removal of the aluminum oxide coating is immersed as a cathode in a Sn plating bath containing 0.3 to 0.5 mol / L of stannous sulfate, 0.5 to 0.8 mol / L of sulfuric acid, 0.15 to 0.3 mol / L of cresol sulfonic acid, 0.003 to 0.007 mol / L of β-naphthol, and 1 to 3 g / L of gelatin. After immersion, the steel sheet is immersed in a current density of 0.5 to 5 A / dm 2 The current flow time is controlled so that the Sn plating can be formed to a thickness of more than 300 nm. A tin plate is preferably used as the anode. The pH of the Sn plating bath is preferably 1.2 to 3.0, and the temperature of the Sn plating bath is preferably 15 to 30°C.
[0111] When the surface plating layer 4 is made of a plating mainly composed of multiple elements such as Sn-Ni plating, Sn-Zn plating, or Sn-Ni-Zn plating, it is preferable to heat the metal with an electron beam using a deposition device to perform alloy plating. The amount of deposition is determined by the vapor pressure at the heating temperature. Therefore, in order to obtain an alloy plating of more than 300 nm, it is preferable to adjust the heating temperature of each metal.
[0112] <Hot stamping process> The steel sheet for hot stamping manufactured as described above can be hot stamped to obtain a hot stamped member. Hereinafter, an example of hot stamping conditions will be described, but the hot stamping conditions are not limited to these conditions.
[0113] The above-mentioned hot stamping steel sheet is placed in a heating furnace and heated at a heating rate of 1.5°C / sec to 10.0°C / sec to a temperature (ultimate temperature) of the Ac3 point or higher. If the heating temperature is 1.5°C / sec to 10.0°C / sec, surface diffusion of Fe can be prevented. If the ultimate temperature is the Ac3 point or higher, springback can be suppressed, which is preferable. The Ac3 point (°C) is expressed by the following formula (1). Ac3=912-230.5×C+31.6×Si-20.4×Mn-14.8×Cr-18.1×Ni+16.8×Mo-39.8×Cu...(1) In the above formula, the element symbol indicates the content of the element in mass %, and 0 is substituted when the element is not contained.
[0114] The holding time after the temperature reaches the target temperature is preferably 5 seconds or more and 300 seconds or less. If the holding time is 5 seconds or more and 300 seconds or less, the diffusion of Fe to the hot stamp surface can be suppressed, which is preferable.
[0115] The steel sheet after the holding is hot stamped and cooled to room temperature to obtain a hot stamped part. The cooling rate from hot stamping to room temperature is preferably 5° C. / sec or more. If the cooling rate is 5° C. / sec or more, the diffusion of Fe to the outermost surface of the hot stamped part can be suppressed.
[0116] If necessary, tempering may be performed after hot stamping, for example, by holding at 250° C. for 30 minutes. EXAMPLES
[0117] Next, an embodiment of the present invention will be described, but the conditions in the embodiment are merely an example of conditions adopted to confirm the feasibility and effects of the present invention, and the present invention is not limited to this example of conditions. Various conditions can be adopted in the present invention as long as they do not deviate from the gist of the present invention and the object of the present invention is achieved.
[0118] (Manufacturing of steel plates) The molten steel having the chemical composition shown in Tables 1A, 1B, 2A, and 2B was cast to produce steel slabs, which were then heated to a temperature of Ac3 to 1400°C and hot-rolled to obtain hot-rolled steel sheets (mother steel sheets). Steel sheets No. 16 and No. 36 were cold-rolled with a cumulative reduction of 50% after hot rolling to a thickness of 3.2 mm to 1.6 mm. In the cases where only hot rolling was performed, the thickness was 1.6 mm by hot rolling. The blanks in Tables 1A, 1B, 2A, and 2B indicate that the element was not intentionally added.
[0119] [Table 1A]
[0120] [Table 1B]
[0121] [Table 2A]
[0122] [Table 2B]
[0123] [Table 3A]
[0124]
Table 3B
[0125]
Table 3C
[0126]
Table 3D
[0127]
Table 4A
[0128]
Table 4B
[0129]
Table 4C
[0130]
Table 4D
[0131]
Table 5A
[0132]
Table 5B
[0133]
Table 5C
[0134] [Table 5D]
[0135] [Table 6A]
[0136] [Table 6B]
[0137] [Table 6C]
[0138] [Table 6D]
[0139] (Al-Si plating) The base steel sheet produced above was subjected to Al-Si alloy plating. The components of the Al-Si alloy plating bath were adjusted so that the Al content and Si content were as shown in Tables 3A, 3B, 3C, and 3D. The base steel sheet produced by the above method was immersed in the plating bath with the adjusted components to obtain the Al-Si alloy plated steel sheet shown in Tables 3A, 3B, 3C, and 3D.
[0140] (Aluminum oxide film removal) The aluminum oxide coating on the surface of the Al-Si alloy plated steel sheet was removed by the method described in Tables 3A, 3B, 3C, and 3D. When "alkali" is described in Tables 3A, 3B, 3C, and 3D, a 0.1 mol / L aqueous solution of sodium hydroxide was used as the removing solution. When "acid" is described in Tables 3A, 3B, 3C, and 3D, a 0.1 mol / L dilute hydrochloric acid was used as the removing solution. The Al-Si plated steel sheet obtained above was immersed in the removing solution to obtain a steel sheet with the aluminum oxide coating removed. When "-" appears in the table, it means that the aluminum oxide coating was not removed.
[0141] (surface plating layer) Next, for steel sheets Nos. 35 and 52 to 58, the Al-Si alloy-plated steel sheets or the Al-Si alloy-plated steel sheets from which the Al oxide coating had been removed were subjected to a treatment to form a surface plating layer by electroplating. When the surface plating layer was Sn plating, the Al-Si alloy-plated steel sheets were immersed in a Sn plating bath containing 0.3 to 0.5 mol / L of stannous sulfate, 0.5 to 0.8 mol / L of sulfuric acid, 0.15 to 0.3 mol / L of cresol sulfonic acid, 0.003 to 0.007 mol / L of β-naphthol, and 1 to 3 g / L of gelatin. After immersion, a tin plate was used as the anode, and a current density of 0.5 to 5 A / dm 2 The current flow time was controlled so that the Sn plating had a thickness of more than 300 nm. The pH of the Sn plating bath was set to 1.2 to 3.0, and the temperature of the Sn plating bath was set to 15 to 30°C.
[0142] In addition, for steel sheets Nos. 1 to 34, 36 to 50, and 59 to 112, a treatment was carried out to form a surface plating layer by deposition on the Al-Si alloy plated steel sheets or the steel sheets from which the aluminum oxide coating had been removed. 3 Distance from the deposition metal source to the steel plate (substrate): 0.6 m; Degree of vacuum during deposition: 5.0×10 -3 ~2.0×10 -5 The deposition was performed under the following conditions: 1 Pa, capacity of the deposition metal source crucible: 40 ml, inner diameter: 30φ, deposition method: electron beam, electron beam irradiation conditions: voltage 10 V (fixed), current 0.7-1.5 A, steel sheet temperature: 50-600°C, steel sheet rotation speed: 15 rpm. Metal with a purity of 99.9 mass% or more was used for the deposition metal. When the structures of the steel sheet, which is the base material of the obtained hot stamping steel sheet, were confirmed by the above-mentioned method, the area ratio of the cross section was ferrite: 20-80%, pearlite: 20-80%, and the remainder: less than 5%.
[0143] (Hot stamping) Next, the steel sheets for hot stamping were hot stamped in a high dew point environment (30° C.) under the conditions shown in Tables 5A, 5B, 5C, and 5D to obtain hot stamped members.
[0144] (Thickness of Al-Si alloy plating layer) The thickness of the Al-Si alloy plating layer was measured as follows. The hot stamping steel sheet obtained by the above manufacturing method was cut in the sheet thickness direction. Then, the cross section of the hot stamping steel sheet was polished, and the polished cross section of the hot stamping steel sheet was linearly analyzed from the surface of the hot stamping steel sheet to the steel sheet using the ZAF method by FE-EPMA, and the Al concentration and Si concentration in the detected components were measured. The measurement conditions were an acceleration voltage of 15 kV, a beam diameter of about 100 nm, an irradiation time per point of 1000 ms, and a measurement pitch of 60 nm. The measurement was performed in a range including the surface plating layer, the Al-Si alloy plating layer, and the steel sheet. The region in which the Si concentration was 3 mass% or more and the sum of the Al concentration and the Si concentration was 95 mass% or more was determined to be the Al-Si alloy plating layer, and the thickness of the Al-Si alloy plating layer was the length in the sheet thickness direction of the above region. The thickness of the Al-Si alloy plating layer was measured at five positions spaced apart by 5 μm, and the arithmetic average of the values obtained was taken as the thickness of the Al-Si alloy plating layer. The evaluation results are shown in Tables 3A, 3B, 3C, and 3D.
[0145] (Measurement of Al and Si contents in Al-Si alloy plating layer) The Al content and the Si content in the Al-Si alloy plating layer were obtained by taking a test piece and measuring the Al content and the Si content at the 1 / 2 position of the total thickness of the Al-Si alloy plating layer according to the test method described in JIS K 0150 (2005) to obtain the Al content and the Si content in the Al-Si alloy plating layer of the hot stamping steel sheet 10. The obtained results are shown in Tables 3A, 3B, 3C, and 3D.
[0146] (Thickness of aluminum oxide film) The thickness of the aluminum oxide coating was evaluated by alternately repeating Ar sputtering and X-ray photoelectron spectroscopy (XPS) measurement. Specifically, the hot stamping steel sheet was sputtered by Ar sputtering (accelerating voltage 0.5 kV, sputtering rate 0.5 nm / min based on SiO2), and then XPS measurement was performed. The XPS measurement was performed using an Al Kα radiation source at an output of 15 kV, 25 W, a spot size of 100 μm, 10 scans, and a total energy range of 0 to 1300 eV. Ar sputtering and XPS measurement were alternately performed, and these measurements were repeated until the peak of the binding energy of the Al 2p orbital of 73.8 eV to 74.5 eV appeared in the XPS measurement and disappeared. The thickness of the aluminum oxide coating was calculated from the sputtering time and sputtering rate from the position where the O content becomes 20 atomic% or more for the first time after the start of sputtering to the position where the O content becomes less than 20 atomic%. The sputtering rate was calculated as SiO2. The thickness of the aluminum oxide coating was the arithmetic average value measured at two points. The results are shown in Tables 3A, 3B, 3C, and 3D.
[0147] (Thickness of surface plating layer) The average layer thickness (thickness) of the surface plating layer 4 can be measured by glow discharge optical emission spectrometry (GDS). The discharge conditions were 35 W (constant power mode), the Ar pressure during measurement was 600 Pa, and the discharge range was 4 mmφ. The distance between the electrodes was 0.18 mm. The measurement time at one point was measured as the time (α) until 90% or more of Fe was detected, and then about 20% of that time (α×0.2) was further measured (total α+0.2α). Measurement was performed up to the region where Al was detected from the outermost surface of the hot stamping steel sheet 10 and the total of the plating components (Sn, Zn, Ni) which are the surface plating layer was 50%. The thickness (nm) of the surface plating layer was obtained as follows. First, the depth cut per unit time was calculated from the depth cut from the start to the end of the measurement and the measurement time. Next, the thickness of the surface plating layer of the hot stamping steel sheet 10 was calculated by multiplying the obtained depth cut per unit time by the measurement time. The results obtained are shown in Tables 4A, 4B, 4C and 4D.
[0148] (Sn content, Zn content, Ni content of surface plating layer) The content of the main element in the surface plating layer (the content of any one of Sn, Zn, and Ni) was determined as the largest element concentration among Sn, Zn, and Ni concentrations at the center position in the sheet thickness direction of the surface plating layer obtained by measuring the thickness of the surface plating layer. Specifically, the arithmetic average (N=2) of the values obtained by measuring at the center position of the surface plating layer in the sheet thickness direction was determined as the largest element content among Sn, Zn, and Ni contents. The results are shown in Tables 4A, 4B, 4C, and 4D.
[0149] (Coverage rate of surface plating layer) The coverage of the surface plating layer was evaluated by XPS measurement. XPS measurement was performed by scanning the hot stamping steel sheet 10 in the full energy range of 0 to 1300 eV using an Al Kα ray source, with an output of 15 kV, 25 W, a spot size of 100 μm, and 10 scans. In the case of Sn plating, the Sn content (atomic%) and the Al content (atomic%) were calculated. Next, the ratio (mass%) of the Ni content to the total of the Sn content (mass%) and the Al content (mass%) was calculated, and the obtained ratio was taken as the coverage (%) of the Sn plating. In the case of alloy plating, the Sn content (atomic%), the Zn content (atomic%), the Ni content (atomic%), and the Al content (atomic%) were calculated. Next, the ratio (%) of the Zn content to the total of the Zn content and the Al content was calculated, and the obtained ratio was taken as the coverage (%) of the alloy plating. The obtained results are shown in Tables 4A, 4B, 4C, and 4D.
[0150] (Depth profile of plating layer) The depth profile of each element in the plating layer of the hot stamped component was obtained by measuring with GDS. The conditions were an electrode distance of 0.19 mm, and high frequency was applied from the back of the sample. The discharge voltage was 35 W (constant power mode), the Ar pressure during measurement was 600 Pa, and the discharge range was 4 mmφ. The measurement time for one location was approximately 12 minutes, and etching was performed by approximately 50 μm. The depth of the plating layer was calculated using the method described above. The depth profile of each element was obtained by measuring from the surface of the hot stamped component to the region where the Fe element of the base material is stable.
[0151] In the region from the surface of the plating layer of the hot stamped member to a position 100 nm from the surface of the plating layer of the hot stamped member in the thickness direction, the Fe content was rated as I, the Fe content was rated as more than 5 mass% and less than 10 mass%, and the Fe content was rated as III. In addition, the maximum value of the sum of the Sn content, Ni content, and Zn content was rated as I, the maximum value of the sum of the Sn content, Ni content, and Zn content was rated as II, the maximum value of the sum of the Sn content, Ni content, and Zn content was rated as II, the maximum value of the sum of the Sn content, Ni content, and Zn content was rated as III, the maximum value of the sum of the Sn content, Ni content, and Zn content was rated as I ... II, the
[0152] In the region from 100 nm in the thickness direction from the surface of the plating layer of the hot stamped component to 500 nm in the thickness direction from the surface of the plating layer of the hot stamped component, the Fe content was rated I when it was 15 mass% or less, II when it was more than 15 mass% and 40 mass% or less, and III when it was more than 40 mass%. In addition, the maximum value of the sum of the Sn content, Ni content, and Zn content was rated I when it was 10 mass% or more, II when it was 5 mass% or more and less than 10 mass%, and III when it was less than 5 mass%.
[0153] In the region from 500 nm in the thickness direction from the surface of the plating layer of the hot stamped component to 1000 nm in the thickness direction from the surface of the plating layer of the hot stamped component, the Fe content was 20 mass% or less, II was 20 mass% or more and 50 mass% or less, and III was more than 50 mass%. In addition, the maximum sum of the Sn content, Zn content, and Ni content was 5 mass% or more, II was 1 mass% or more and less than 5 mass%, and III was less than 1 mass%. In Tables 6A, 6B, 6C, and 6D, the region from the surface to 1000 nm was judged as passing when all regions were I or II, and rated as G. In the judgment of each region, when even one region was III, it was rejected and rated as B. In the tables, Sn+Ni+Zn means the total (mass%) of Sn content, Ni content, and Zn content.
[0154] The region (0-100 nm) in Tables 6A, 6B, 6C, and 6D refers to the region from the surface of the plating layer to a position 100 nm from the surface of the plating layer in the thickness direction. The region (100-500 nm) in Tables 6A, 6B, 6C, and 6D refers to the region from a position 100 nm from the surface of the plating layer in the thickness direction to a position 500 nm from the surface of the plating layer in the thickness direction. The region (500-1000 nm) in Tables 6A, 6B, 6C, and 6D refers to the region from a position 500 nm from the surface of the plating layer in the thickness direction to a position 1000 nm from the surface of the plating layer in the thickness direction.
[0155] (At least one of Sn oxide, Sn hydroxide, Ni oxide, Ni hydroxide, Zn oxide, and Zn hydroxide in a region from the surface of the plating layer to a position 20 nm from the surface of the plating layer in the thickness direction) The presence of at least one of Sn oxide, Sn hydroxide, Ni oxide, Ni hydroxide, Zn oxide, and Zn hydroxide in the region from the surface of the plating layer to a position 20 nm from the surface of the plating layer in the thickness direction was confirmed by X-ray photoelectron spectroscopy measurement (XPS measurement). Specifically, the hot stamped member was sputter-etched by Ar sputtering (accelerating voltage 20 kV, sputter rate 1.0 nm / min), and then XPS measurement was performed. The XPS measurement was performed by scanning the outermost surface of the hot stamped member over the entire energy range using an ULVAC-PHI Quantum2000 type, an Al Kα ray source, an output of 15 kV, 25 W, a spot size of 100 μm, and 10 scans. The Ar sputtering etching and XPS measurement were performed alternately, and these measurements were repeated from the plating layer to a position 20 nm in the thickness direction. The depth from the surface of the plating layer was calculated from the sputtering etching time and the sputtering rate. When a peak is detected in the range of any of the above-described Sn oxide, Sn hydroxide, Ni oxide, Ni hydroxide, Zn oxide, or Zn hydroxide in the region from the surface of the plating layer of the hot stamped member to the position 20 nm from the surface of the plating layer in the thickness direction, it is determined that at least one of Sn oxide, Sn hydroxide, Ni oxide, Ni hydroxide, Zn oxide, or Zn hydroxide is present on the surface of the plating layer. The sputter etching rate was calculated in terms of SiO2. The total of the Sn content, Ni content, and Zn content in the region from the surface of the plating layer of the hot stamped member to the position 20 nm from the surface of the plating layer in the thickness direction was calculated from all elements detected by XPS measurement.
[0156] (Determination of the area up to 20 nm from the surface) In the region from the surface of the plating layer to a position 20 nm from the surface of the plating layer in the thickness direction, at least one of Sn oxide, Sn hydroxide, Ni oxide, Ni hydroxide, Zn oxide, and Zn hydroxide was present, and the sum of the Sn content, Ni content, and Zn content was 30 mass% or more, the case was rated G, and the other cases were rated B. The results are shown in Tables 6A, 6B, 6C, and 6D. (Determination of each rich area) From the GDS measurement results of the depth profile of each element of the plating layer of the hot stamped component, the plating layer was classified into the following cases (judgment of each rich region) in the order of the surface rich region (total of Sn content, Ni content and Zn content: 50 mass% or more, Sn content: 7 mass% or more, Ni content: less than 72 mass%, and Zn content: less than 40 mass%), Al rich region (Al content: 10 mass% or more, Fe content: 50 mass% or less), and Fe rich region (Al content: 10 mass% or more, Fe content: more than 50 mass%) from the surface of the plating layer in this order (judgment of each rich region), and the case where these regions were not included was classified into B. The obtained results are shown in Tables 6A, 6B, 6C, and 6D.
[0157] (Tensile strength) The tensile strength of the hot stamped parts was measured by preparing No. 5 test pieces as specified in JIS Z 2241:2011 from any position of the hot stamped parts and measuring the strength according to the test method as specified in JIS Z 2241:2011. Note that the test No. 49, in which the condition of the scale was poor, was not evaluated. The measurement results are shown in Tables 5A, 5B, 5C, and 5D.
[0158] (Amount of hydrogen absorbed in the heating furnace) The hot stamped parts were subjected to a temperature rise hydrogen analysis to measure the amount of hydrogen in the hot stamped parts. After hot stamping, the hot stamped parts were immersed in liquid nitrogen when the temperature dropped to about 100°C, and frozen by cooling to below -10°C. The amount of diffusible hydrogen released by the temperature rise hydrogen analysis up to 300°C was used to evaluate the amount of hydrogen that penetrated into the hot stamped parts (mass ppm). The amount of hydrogen that penetrated was 0.2wt.ppm or less was rated as E, 0.20wt.ppm to 0.35wt.ppm as Gr, 0.35wt.ppm to 0.6wt.ppm as G, and over 0.6wt.ppm as B. The cases rated as E, Gr, and G were judged to be able to suppress the amount of hydrogen that penetrated even in a high dew point environment, and were therefore considered to have passed. The case of B was considered to have failed. The measurement results are shown in Tables 5A, 5B, 5C, and 5D. Note that the amount of hydrogen that penetrated was not evaluated for steel sheets that broke early and had a tensile strength of less than 1600MPa.
[0159] (Amount of hydrogen infiltrated into hot stamped parts (exposure test)) Some hot stamped parts were held at 60℃ for 3 days to remove hydrogen, then exposed to an environment within 0.5km of the coast of Okinawa for 6 months, and the amount of hydrogen absorbed into the hot stamped parts was investigated. The thermal desorption method was performed with a sample size of 10x40mm, a temperature rise range of room temperature to 200℃, and a temperature rise rate of 100℃ / h, and the cumulative amount up to 200℃ was calculated. When the cumulative amount of hydrogen was 0.7 wt.ppm or more, it was evaluated as Bad (B), and when it was less than 0.7 wt.ppm, it was evaluated as Good (G). The results are shown in Tables 5A, 5B, 5C, and 5D.
[0160] As shown in Tables 5A, 5B, 5C, and 5D, steel sheets Nos. 21, 22, 25, 26, 32, 42, 57, 58, 63 to 66, 71 to 109, 111, and 112, which satisfy the range of the present invention, had small amounts of absorbed hydrogen in the heating furnace and after hot stamping. Comparative Example 20 and the like had a Zn concentration of 50 mass% or more, so the amount of absorbed hydrogen after hot stamping was high. [Industrial Applicability]
[0161] According to the present invention, even in the case of an Al-plated steel sheet for hot stamping and in the case of hot stamping in a high dew point environment, the amount of absorbed hydrogen is reduced, thereby providing excellent hydrogen embrittlement resistance, and therefore the present invention has high industrial applicability. [Explanation of symbols]
[0162] 1 steel plate 2. Al-Si alloy plating layer 3 Al oxide coating 4 Surface plating layer 10. Steel sheets for hot stamping
Claims
1. A hot stamped member comprising a base steel material and a plating layer provided on the base steel material, the plating layer comprising: a surface-rich region in which the sum of the Sn content, the Ni content, and the Zn content is 50% by mass or more, the Sn content is 7% by mass or more, the Ni content is less than 72% by mass, and the Zn content is less than 40% by mass; an Al-rich region in which the sum of the Sn content, the Ni content, and the Zn content is less than 50 mass%, the Al content is 10 mass% or more, and the Fe content is 50 mass% or less; An Fe-rich region having an Al content of 10 mass% or more and an Fe content of more than 50 mass%; in this order from the surface of the plating layer, In a region from the surface of the plating layer to a position 100 nm from the surface of the plating layer in a thickness direction, The maximum total value of the Sn content, the Ni content, and the Zn content is 50 mass% or more; The Fe content is 10% by mass or less, In a region from a position 100 nm from the surface of the plating layer in the thickness direction to a position 500 nm from the surface of the plating layer in the thickness direction, The maximum total value of the Sn content, the Ni content, and the Zn content is 5 mass% or more; The Fe content is 40% by mass or less, In a region from a position 500 nm from the surface of the plating layer in the thickness direction to a position 1000 nm from the surface of the plating layer in the thickness direction, The maximum total value of the Sn content, the Ni content, and the Zn content is 1 mass% or more; The Fe content is 50% by mass or less. A hot stamped member characterized by:
2. The Ni content in the surface rich region is less than 50 mass%.
2. The hot stamped component according to claim 1 .
3. In a region from the surface of the plating layer to a position 20 nm from the surface of the plating layer in the thickness direction, 3. The hot stamped member according to claim 1, characterized in that at least one of Sn oxide, Sn hydroxide, Ni oxide, Ni hydroxide, Zn oxide, and Zn hydroxide is present, and a total of the Sn content, the Ni content, and the Zn content is 30 mass% or more.
4. The chemical composition of the base steel material is, in mass%, C: 0.25-0.70%, Si: 0.005-1.000%, Mn: 0.30-3.00%, P: 0.100% or less, S: 0.1000% or less, N: 0.0100% or less, Cu: 0 to 1.00%, Ni: 0 to 1.00%, Cr: 0-1.000%, Mo: 0-1.000%, Nb: 0 to 0.200%, V: 0 to 1.00%, Ti: 0 to 0.150%, B: 0 to 0.0100%, Co: 0-1.00%, W: 0-1.00%, Sn: 0-1.00%, Sb: 0 to 1.00%, Zr: 0 to 1.00%, Mg: 0 to 0.150%, Al: 0 to 1.0000%, Ca: 0-0.010%, REM: 0% to 0.300%, and The balance is Fe and impurities. The hot stamped member according to any one of claims 1 to 3.
5. The chemical composition of the base steel material is, in mass%, Cu: 0.01 to 1.00%, Ni: 0.01-1.00%, Cr: below 0.001-1.000%, Mo: 0.001 to 1.000%, Nb: 0.001-0.200%, V: 0.01 to 1.00%, Ti: 0.001 to 0.150%, B: 0.0010 to 0.0100%, Co: 0.01 to 1.00%, W: 0.01-1.00%, Sn: 0.01-1.00%, Sb: 0.01 to 1.00%, Zr: 0.01 to 1.00%, Mg: 0.001-0.150%, Al: 0.0010-1.0000%, Ca: 0.001 to 0.010%, and REM: 0.001~0.300% Contains one or more selected from the group consisting of 5. The hot stamped component according to claim 4.
Citation Information
Patent Citations
Rust preventing steel sheet for fuel tank
JP1987230987A
Rust preventing steel sheet for fuel tank
JP1987230988A
Surface-treated steel sheet with high strength superior in corrosion resistance after being painted, and car components with high strength
JP2004124208A
Al-PLATED STEEL MATERIAL TO BE HOT-PRESSED WHICH IS EASILY HEATED, HAS SUPERIOR WORKABILITY AND HAS SUPERIOR CORROSION RESISTANCE AFTER HAVING BEEN COATED
JP2007302982A
Coated heat-treated steel product, and method for manufacturing the same
JP2012062500A